Antioxidant Content and Vitamin C in Mango Leaf Kombucha with Stevia Sweetener and Different Fermentation Durations - Ambarwati, Ambarwati; Martiana, Icha Saldela; Rachmah, Salma Azhary (Universitas Malahayati, 2024)
ABSTRACT Kombucha is made by the symbiotic fermentation of acetic acid bacteria and a species of yeast known as a SCOBY. Sucrose is converted by bacteria and yeast into organic acids such as acetic acid and glucuronic acid, amino acids, antibiotics, and various micronutrients during the fermentation process. The aim of this research was to determine the physical properties, pH, antioxidant content, and vitamin C and mango leaf Kombucha with stevia sweetener and variations in fermentation time. This research used a Completely Randomized Design (CRD), kombucha used stevia sweetener and used two variations of fermentation time, namely 11 and 13 days. The results showed that the physical properties of mango leaf kombucha showed a brownish color, sweet taste and became very sour. The pH of kombucha at 11 days of fermentation was 4 and 13 days was 4. The antioxidant content at 11 days of fermentation was 79.02% while at 13 days it was 84.97%. The Vitamin C content at 11 days of fermentation was 63.42%, while at 13 days it was 67.96%. Thus, it can be concluded that the fermentation time affects the antioxidant and Vitamin C content of mango leaf kombucha. Keywords: Antioxidants, Vitamin C, Kombucha, Long Fermentation Time